PENGUJIAN BERAS AKING SEBAGAI BAHAN MAKANAN - Bambang N.; Heri R. M.; Tita R.; Suryana Purawisastra (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2008)
The Study On The Used Rice as Staple Food.Background: Due to the high price of rice, some people used the used rice known as "beras aking" as staple food replacing the rice. The rice was cooked similar to the cooking of original rice. In its preparation to become aking, the cooked rice firstly is dried under the sun until the rice becoming dry. Consequently, the appearance of the rice is brownness color and sometime already grown by the mold. However, the people are preferred to choose the aking than other alternate food such as cassava. Therefore we performed to study the nutrition and acceptability of the used rice through the chemical analysis, microbial observation and sensory evaluation of the cooked of used rice.Objectives: The objective of this study is to asses the uses rice as staple food.Methods: Five samples of the used rice were obtained from district of Cirebon, Sumedang, Cileles, Indramayu and Bandung. The method of study is descriptive method to examine the characteristic of used rice by comparing with the ordinary rice.Results: As the consequent in preparation of the used rice, its content of moisture, pH, density and whiteness were low than those of ordinary rice. In addition, the content of reducing sugar was a bit higher than these of original rice. However, the protein content of used rice showed the various result, two samples of them had protein content less than the usual rice's while the rest three samples had protetn content higher than the ordinary rice's. The content of ash and total count of microbial in the used rice was seemly not different from the usual rice's However, the growth of microbial during preparation of the used rice was observed. Therefore, the examination of toxic substance should be done. The color, texture and aroma of the used rice were assessed lower than those of the ordinary rice in descriptive analysts. The steamed used rice had brownish white color, very soft texture and enough annoying acid aroma. Conclusion: The quality of used rice could be increased both nutritionally and its acceptance. Mixing the used rice with other ingredient and the more controlled drying process and good raw material would increase the quality of the used rice. In addition, the examination of toxic substance produced the micro organism should be done, since the micro organism growth during the preparation of used rice.Keywords: the used rice, beras aking.